2012
DOI: 10.1007/s11033-012-2371-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of NADP+-dependent isocitrate dehydrogenase from Microcystis aeruginosa PCC7806

Abstract: Microcystis aeruginosa is the key symptom of water eutrophication and produces persistent microcystins. Our special attention was paid to the isocitrate dehydrogenase (IDH) of M. aeruginosa (MaIDH) because it plays important roles in energy and biosynthesis metabolisms and its catalytic product 2-oxoglutarate provides the carbon skeleton for ammonium assimilation and also constitutes a signaling molecule of nitrogen starvation in cyanobacteria. Sequence alignment showed that MaIDH shared significant sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…The samples without added manganese showed a 25% of the control activity (complete mixture), while those where manganese was replaced by magnesium had roughly half of the control activity, indicating a preference of ICDH for the manganese ion. Similar results have been observed in other bacteria, including cyanobacteria [36], [38], [39], [53], [54]. In a series of assays at different temperatures, we observed that ICDH activity increased continuously from 30 to 55°C, but at the same time it became less stable: preincubation of the cell extracts at different temperatures showed that the activity decreased sharply above 35°C.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The samples without added manganese showed a 25% of the control activity (complete mixture), while those where manganese was replaced by magnesium had roughly half of the control activity, indicating a preference of ICDH for the manganese ion. Similar results have been observed in other bacteria, including cyanobacteria [36], [38], [39], [53], [54]. In a series of assays at different temperatures, we observed that ICDH activity increased continuously from 30 to 55°C, but at the same time it became less stable: preincubation of the cell extracts at different temperatures showed that the activity decreased sharply above 35°C.…”
Section: Resultssupporting
confidence: 89%
“…9.0–9.5. This value is close to those described for other NADP-ICDH [35][38], [55][57], with the exception of M. aeruginosa , which had an optimum pH of 7.5 [39], although it has to be taken into account that this was a recombinant enzyme.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations